An Electronic Current Transformer Based on Rogowski Coil - Faifer, M.; Ottoboni, R. (2008 IEEE Instrumentation and Measurement Technology Conference, 2008)
In the industrial world the quality of the electric power is becoming very critical. In order to verify this requirement, new measurement systems should be installed at various levels of the power network, capable to measure over a wide frequency range the current and voltage harmonics with a proper accuracy. When high voltage power systems are taken into account, this requirement is very difficult to achieve using traditional measurement devices, mainly due to the bandwidth limitations of this kind of transducers. For this reason in the last years several research activity have been especially focused on the study and the development of new measurement systems for high-voltage networks. In particular, in this paper a current transformer based on Rogowski coils for high voltage systems is presented, fulfilling the features required for power quality analysis. The adopted transformer architecture, which is based on digital processing techniques, permits to overcome the typical problem concerning the use of Rogowski coils as current transducer.